Tensile Property of Melt Mixing Co-Polypropylene with Waste Polymer at Different Composition Ratios - A. Sufian, N.; Z. M. Rus, A.; Shahrizan Syah, A.; Hazwanee M. J, Farhana; M, Noraini; Aida I, S. (International Journal of Engineering and Technology, 2018)
In order to implement economical way of managing unwanted substances, waste polymer (WP) can be recycled instead of throwing it away. It can be reused via "sink-float" technique and mixed with another binder like co-polypropylene (co-PP) to enhance the mechanical properties of the material. This is because co-PP is a bit softer but has better impact strength, much tougher and more durable than polypropylene (PP). Two materials underwent injection moulding with 170Â°C temperature to produce dog bone samples for tensile test. The test started with 10% up until 80% of WP content mixed with co-PP. Tensile test speed used for this experiment was 5mm/s. Stress vs. strain graph was obtained from the test and the modulus of elasticity was obtained by using the stress over strain formula. The stress versus strain result for the composite with WP is lower than that of co-PP, proving that WP is more brittle compared to the more elastic co-PP. Morphological analysis of surface structure based on Optical Microscope (OM) indicates that co-PP has smooth surface while WP has a rough surface.Â Â